Needs Assessment for the Development of Soft Skills to Enhance Essential Soft Skills for Work in the Aviation Industry: A Case Study of Aviation Business Management Students at Chiang Mai Rajabhat University - Maneerat, Phichaya (Journal of Graduate Research, 2025)
Hard skills and soft skills play a crucial role in workforce efficiency in the modern aviation industry, which has been significantly impacted by digital technology and the COVID-19 pandemic. As a result, the remaining job positions increasingly require soft skills, which technology cannot replace. The development of soft skills should begin at the university level. Although soft skills are considered essential for work, research on soft skills in the aviation industry and student development remains limited. This study aimed to: 1) identify the soft skills necessary for working in the aviation industry; 2) conduct a needs assessment to prioritize the ranking of soft skills required for working in the aviation industry among students in the Aviation Business Management Program at Chiang Mai Rajabhat University; and 3) propose active learning methods to enhance students’ soft skills based on prioritized needs. A mixed-method research design was employed, consisting of three phases: 1) qualitative research involving with a literature review to identify the necessary soft skills for work, followed by in-depth interviews with airline and airport service personnel to determine the essential soft skills required in the aviation industry; 2) quantitative research using the Modified Priority Needs Index and paired t-test to assess and rank students’ soft skill needs; and 3) classroom research proposing active learning management methods to enhance students’ soft skills. Research instruments included interviews, questionnaires, pre-tests and post-test, and the 6-step process of problem-based learning management. The quantitative data were analyzed using descriptive statistics including percentage, mean, and standard deviation. Inferential statistics included pair t-tests, and the Modified Priority Needs Index. The findings revealed the top five essential soft skills in the aviation industry: 1) communication, 2) leadership, 3) creativity, 4) complex problem-solving, and 5) teamwork. The Priority Needs Index (PNI) analysis showed students’ top five soft skills development needs as 1) complex problem-solving, 2) communication, 3) leadership, 4) creativity, and 5) teamwork. Implementation of the problem-based learning model showed a significant difference between pre-test and post-test scores at the .05 significance level, indicating its effectiveness in developing students’ complex problem-solving skills. The research results can be applied as a guideline for curriculum development, student preparation for the workforce, and development in the aviation industry personnel.